Comparative Evaluation of the Effects of Different Sterilization Methods on Cyclic Fatigue Resistance of NiTi Files: An in vitro Study - Narwal, Poonam; Sheoran, Kitu; Kaushik, Mamta; Reddy, Pallavi; -, Roshni; -, Narmatha (Journal of Orofacial Research, 2015)
evaluated. A total of new 50 ProTaper files nickel-titanium (NiTi) files (Tulsa-dentsply, USA), of standard # 20 size with taper of 0.06 and 25 mm length were taken, and divided into five groups according to method of sterilization employed with 10 files in each group. Group 1: Control with no sterilization of files. Group 2: Autoclaved files at 121ºC at 15 psi for 15 minutes. Group 3: Files wiped with 90% ethyl alcohol solution. Group 4: Files submerged in glass bead sterilizer at 425º Ffor 10 seconds. Group 5: Files immersed in 2% glutaral dehyde solution for 4 hours. After five cycles of sterilization, in custom made cyclic fatigue testing model, time taken for fracture of files and number of cycles to failure (NCF) was calculated in each group. Results were analyzed statistically using analysis of variance (ANOVA) test at the 95% confidence level (p < 0.05). Conclusion: Changes in the mechanical properties of NiTi endodontic instruments after five cycles of common sterilization procedures were insignificant.